2018
DOI: 10.1021/acs.jpcc.8b00793
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Predictive Power of Density Functional Theory in Finite-Temperature Hydrogen Adsorption/Desorption Thermodynamics

Abstract: Density functional theory (DFT) has been widely employed to study the gas adsorption properties of surfacebased or nanoscale structures. However, recent indications raise questions about the trustworthiness of some literature values, especially in terms of the DFT exchange−correlation (XC) functional. Using hydrogen adsorption on metalloporphyrinincorporated graphenes (MPIGs) as an example, we diagnosed the trustworthiness of DFT results, meaning the range of expected variations in the DFT prediction of experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Yoon et al studied the contribution of vibrational energies to free energies of H 2 on metalloporphyrin-incorporated graphene using LDA, GGA, and vdW functionals. 121 For weak adsorptions, the zero-point energy and vibrational free energy significantly depend on the choice of vdW functionals (see Figure 9). For the Zn case, the difference of vibrational free energy of adsorbed H 2 is ca.…”
Section: Applications Of Vdw Approaches For Studies Of Adsorption Cat...mentioning
confidence: 99%
“…Yoon et al studied the contribution of vibrational energies to free energies of H 2 on metalloporphyrin-incorporated graphene using LDA, GGA, and vdW functionals. 121 For weak adsorptions, the zero-point energy and vibrational free energy significantly depend on the choice of vdW functionals (see Figure 9). For the Zn case, the difference of vibrational free energy of adsorbed H 2 is ca.…”
Section: Applications Of Vdw Approaches For Studies Of Adsorption Cat...mentioning
confidence: 99%
“…We justify the limitation of our approach by the fact that the binding energies in eqn ( 2) are the DFT values at 0 K. In principle, realistic adsorption energies at finite temperatures require the exhaustive inclusion of the molecular vibrational free energy of the gas adsorbates. 49 This contribution is generally ignored, and it is speculated that the immense chemical bonds (i.e., strong binding energies) of gas/ sensor interfaces yield negligible molecular vibrational energy. However, a recent study showed that prominently chemisorbed diatomic radicals (e.g., OH) possess a significant vibrational free energy of 100 meV at room temperature.…”
Section: Resultsmentioning
confidence: 99%